2021
DOI: 10.1088/2515-7639/abf7dd
|View full text |Cite
|
Sign up to set email alerts
|

Nanophotosensitizers for cancer therapy: a promising technology?

Abstract: Photodynamic therapy (PDT) has been clinically applied to cure various diseases including cancer. Indeed, photophrin (porfimer sodium, Axcan Pharma, Montreal, Canada), a heterogenous mixture of porphyrins, was the first photosensitizer (PS) approved for the treatment of human bladder cancer in 1993 in Canada. Over the past 10 years the use of PDT in the treatment of benign and malignant lesions has increased dramatically. However, PDT is still considered as an adjuvant strategy due to its limitations, primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 182 publications
0
12
0
Order By: Relevance
“…Compared to the free molecular conventional PSs, nano-formulations of PSs impart certain unique and improved properties that make them more potent for PDT applications. First of all, nanomaterials act as a stable and potent drug delivery carrier which generally overcomes the shortcomings of free molecular PSs like hydrophobicity, aggregations, and low tumor cell/tissue specificity, and further permits higher loading of PSs allowing controlled delivery and accumulation in tumor mass in higher concentrations (Zhang et al, 2016;dos Santos et al, 2021;Yan et al, 2020). The smaller size and stability of NPs prolongs the circulation of PSs in the system, enables passive targeting and higher accumulation of PSs in the tumor mass by enhanced permeation and retention (EPR) effect, whereby the leaky and improperly generated tumor vasculatures allow enhanced penetration of circulating NPs in tumor tissues.…”
Section: Nano-photosensitizersmentioning
confidence: 99%
“…Compared to the free molecular conventional PSs, nano-formulations of PSs impart certain unique and improved properties that make them more potent for PDT applications. First of all, nanomaterials act as a stable and potent drug delivery carrier which generally overcomes the shortcomings of free molecular PSs like hydrophobicity, aggregations, and low tumor cell/tissue specificity, and further permits higher loading of PSs allowing controlled delivery and accumulation in tumor mass in higher concentrations (Zhang et al, 2016;dos Santos et al, 2021;Yan et al, 2020). The smaller size and stability of NPs prolongs the circulation of PSs in the system, enables passive targeting and higher accumulation of PSs in the tumor mass by enhanced permeation and retention (EPR) effect, whereby the leaky and improperly generated tumor vasculatures allow enhanced penetration of circulating NPs in tumor tissues.…”
Section: Nano-photosensitizersmentioning
confidence: 99%
“…Conventional PDT, like other traditional therapies, has also been associated with recurrence and resistance [69]. The possible mechanism of resistance to PDT may be attributed to several properties, such as inherent tumour heterogeneity and drug efflux [69,70]. Nonetheless, studies have reported that a cancer cell population that is resistant to chemotherapeutic treatment, to some extent, can be slightly more susceptible to PDT [70].…”
Section: Current Limitations Of Crc Pdtmentioning
confidence: 99%
“…The possible mechanism of resistance to PDT may be attributed to several properties, such as inherent tumour heterogeneity and drug efflux [69,70]. Nonetheless, studies have reported that a cancer cell population that is resistant to chemotherapeutic treatment, to some extent, can be slightly more susceptible to PDT [70]. The recurrence and progression of colorectal cancer (CRC) has been linked to the presence of cancer stem-like cells (CSCs) that exhibit a high resistance to PDT [35].…”
Section: Current Limitations Of Crc Pdtmentioning
confidence: 99%
See 2 more Smart Citations